Perbandingan Kedudukan Hukum Perceraian di Luar Pengadilan Indonesia dan Pakistan: Perspektif Fikih dan Hukum Positif - Nandi Yosep Kustiwa; Ahmad Nurjaman; Muhamad Ramdhan; Sisca Lestari; Encum Sumirah (Penerbit Lestari Sakha Pustaka, 2026)
This study provides a comparative analysis of the legal standing of extra-judicial divorce (talak) in Indonesia and Pakistan, examining the divergence between classical Islamic jurisprudence (fiqh) and modern positive law. While classical fiqh grants husbands a unilateral right to divorce effective upon pronouncement, the codification of family law in both nations has created a legal dualism. This phenomenon, where a divorce may be valid religiously but not legally, generates significant legal uncertainty and social vulnerability, particularly for women and children regarding their post-divorce rights. This research employs a normative-comparative legal approach, analyzing primary legal sources Indonesia's Law No. 1 of 1974 and Compilation of Islamic Law (KHI), and Pakistan's Muslim Family Laws Ordinance (MFLO) of 1961 alongside classical fiqh texts. The findings reveal two distinct regulatory philosophies. Indonesia adopts a judicial invalidation model, where any divorce outside the court is legally void and without legal effect, centralizing all authority within the judiciary to ensure absolute legal certainty. In contrast, Pakistan implements a sanction-based regulation model. The MFLO 1961 acknowledges the occurrence of extra-judicial talak but mandates a strict reporting procedure to an Arbitration Council and imposes criminal penalties, including imprisonment or fines, for non-compliance. This study concludes that Indonesia's approach provides superior formal legal certainty but struggles with social implementation, leading to limping marriages. Pakistan's pragmatic model offers stronger deterrents through sanctions but faces challenges with low compliance and conservative resistance. The comparison highlights the fundamental dilemma between juridical idealism and social pragmatism in modernizing Islamic family law.